2010
DOI: 10.1002/ajh.21796
|View full text |Cite
|
Sign up to set email alerts
|

Immature Plasmodium falciparum gametocytes in bone marrow

Abstract: A 50-year-old Iraqi man presented with splenomegaly and pyrexia of unknown origin. A bone marrow aspirate was done as part of the investigations and unexpectedly showed Plasmodium falciparum parasites. Malaria had not been suspected as this condition is now rare in Iraq but it subsequently transpired that the patient had recently visited Pakistan.The gametocytes that are observed in the bone marrow differ from those that are observed in the blood, being less mature [1]. The immature gametocytes that are seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…Gametocytes are difficult to quantify in vivo since they sequester in tissues during the majority of their maturation [5860]. Some of the most detailed in vivo dynamical data come from the early 20th century when malaria was used as a therapy for tertiary neurosyphilis [3639].…”
Section: Gametocyte Sequestration: Where Do They Hide?mentioning
confidence: 99%
See 1 more Smart Citation
“…Gametocytes are difficult to quantify in vivo since they sequester in tissues during the majority of their maturation [5860]. Some of the most detailed in vivo dynamical data come from the early 20th century when malaria was used as a therapy for tertiary neurosyphilis [3639].…”
Section: Gametocyte Sequestration: Where Do They Hide?mentioning
confidence: 99%
“…Several studies have observed immature gametocytes in the human bone marrow [59,60,62], but not in highly vascularized organs such as the heart, brain, and placenta [6366], a strikingly different pattern from the sequestration of asexual stages. A recent quantitative analysis further confirmed the enrichment of immature gametocytes in bone marrow [67], although a secondary reservoir in the spleen could not be excluded.…”
Section: Gametocyte Sequestration: Where Do They Hide?mentioning
confidence: 99%
“…Evidence for such enrichment is scarce, with several case reports showing an abundance of immature gametocytes in the spleen and bone marrow. [5][6][7][8] However, these studies are of limited scale and used standard light microscopy as the only method for gametocyte detection and stage differentiation; standard light microscopy is known to have low sensitivity compared with molecular tools 9,10 and to miss a substantial proportion of P falciparum infections in surveys of endemic populations. [11][12][13] The information on gametocyte stages detected by molecular techniques such as polymerase chain reaction (PCR) is scarce for P falciparum infections in peripheral blood and absent for infections in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware, for example of a bone marrow aspirate that was performed to investigate ‘pancytopenia’ that was actually due to a blood sample being taken from above an intravenous infusion, and of another that was done to investigate ‘neutropenia’ that was also factitious, the patient having an inherited myeloperoxidase deficiency that led to the neutrophils not being recognised by an automated instrument. We are aware of instances of malaria being diagnosed from a bone marrow aspirate1; clinical suspicion and careful examination of the peripheral blood should avoid this. Similarly, we are aware of two cases, one of which has been published,2 in which a bone marrow aspiration was performed for suspected autoimmune thrombocytopenic purpura, when careful examination of a blood film subsequently revealed the May–Hegglin anomaly.…”
Section: Bone Marrow Aspiration Is Done When It Is Not Neededmentioning
confidence: 99%